Association Between Irritable Bowel Syndrome and Sleep Disturbance in Adolescents - Indah Kusumawati Noor L; Bakri A; Soejadhi R; Kesuma Y (Dove Medical Press, 2020)
Laili Indah Kusumawati Noor,1 Achirul Bakri,2 Rismarini Soejadhi,2 Yudianita Kesuma2 1Specialist Study Program, Department of Pediatrics, Faculty of Medicine, Universitas Sriwijaya and Moh Hoesin Hospital, Palembang, Indonesia; 2Department of Pediatrics, Faculty of Medicine, Universitas Sriwijaya and Moh Hoesin Hospital, Palembang, IndonesiaCorrespondence: Yudianita KesumaDepartment of Pediatrics, Faculty of Medicine, Universitas Sriwijaya and Moh. Hoesin Hospital, Palembang, IndonesiaTel/Fax +62 711 376445Email erde2704@yahoo.comIntroduction: Sleep disorder in adolescents is a problem that is rarely considered by both parents and healthcare professionals. Ignorance of sleep disorders is likely caused by the very rare occurrence of associated sporadic or emergency cases. Irritable bowel syndrome (IBS) is a functional gastrointestinal disorder characterized by abdominal pain and changes in the defecation pattern. Previous research has demonstrated IBS as one of the many causes of sleep disorders. Difficulty sleeping, frequent awakening, and difficulty returning to sleep after awakening are the symptoms often experienced by adolescents with IBS. The high incidence of IBS in adolescents and the large proportion of sleep disorders in IBS affect the quality of life and disrupt physical development, behaviour, and learning achievement. The relationship between IBS and sleep disorders in adolescents needs to be studied. This study aims to determine the relationship between sleep disorders and IBS in high school adolescents in Palembang.Methods: This is a cross-sectional study conducted on 294 high school adolescents in Palembang in June 2018. Random sampling method was used and the presence of IBS and sleep disturbances were assessed using a questionnaire.Results: Among all subjects, we found 113 subjects (38.4%) with IBS. Of these 113 subjects with IBS, only 60 subjects (53.1%) experienced sleep disorders.Conclusion: No correlation found between sleep disorders and IBS in adolescents.Keywords: irritable bowel syndrome, IBS, sleep disorders, adolescents